Redesign of The Concept of Money in Substitution For Criminal Acts of Corruption in Returning State Losses in Criminal Acts of Corruption - Ricka Debby Indah Sari; Ludfie Jatmiko Setyo Poerwoko; Helvis; Malemna Sura Anabertha Sembiring (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
Corruption in the natural resources sector constitutes an extraordinary crime that causes significant financial losses to the state as well as extensive ecological and social impacts. Within the Indonesian positive legal system, the recovery of state losses is accommodated through an additional criminal sanction in the form of substitute money, as regulated under the Anti-Corruption Law. This study aims to analyze the normative construction of substitute money sanctions, judicial considerations in corruption cases involving tin mining and Harvey Moeis, and their effectiveness within the framework of asset recovery. This research employs a normative legal method using statutory and case approaches. The findings indicate that, normatively, substitute money serves as an imperative instrument for restoring state losses. However, in practice, it remains positioned as a subordinate sanction to imprison. The existence of subsidiary imprisonment and limitations in asset tracing have reduced the effectiveness of recovery efforts. The novelty of this research lies in its conceptual reconstruction that positions substitute money as a primary sanction in corruption sentencing based on asset recovery, rather than merely an accessory punishment. This approach emphasizes the follow the money principle and value-based configuration as the central orientation for restoring state financial losses.